Rooting for info? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
More than three hundred growers and researchers on rootcrops swap information regularly on the RootcropsNet - a forum for advice on tropical root crops. It is intended in particular for research and extension services, scientific organisations,...